Influence of Skydrol immersion at elevated temperatures on the thermo‐mechanical properties of a high‐Tg anhydride epoxy resin toughened with a hydroxy‐terminated polyester. Issue 1 (3rd November 2022) - Hübsch, Jan David; Demleitner, Martin; Bard, Simon; Berendes, Philipp; Altstädt, Volker; Mittelstedt, Christian
Abstract: Currently, the application of composites in aerospace parts exposed to higher temperatures and in aggressive media is still severely limited. To replace metal alloys, alternative resins systems with suitable long‐term heat resistance are needed. In this study, the effect of the aviation hydraulic fluid Skydrol on the thermal and mechanical properties of a high‐Tg, anhydride‐cured epoxy resin in the unmodified and toughened state at elevated temperature is investigated. An aliphatic polyester diol was selected as an intrinsic toughener and its impact on the thermal, mechanical, and aging properties was determined. Experimental characterization of the aging effects is carried out with dynamic‐mechanical characterization, infrared spectroscopy, and electron dispersion x‐ray spectroscopy. In addition, the fracture toughness and the fatigue crack propagation behavior are determined. Initially, the toughened system shows an improved fracture toughness. Since oxidation is blocked by the Skydrol fluid only thermal degradation takes place as determined by the decrease in glass transition temperature Tg and network density. The thermal degradation leads to a tougher behavior, which is observed in both systems in static and dynamic mode with toughness decreasing with aging time again. Abstract :